0288 Role of cofilin and calcium signaling in sleep-loss neural injury. (25th May 2022) - Chou, Allison Tzu-Han; Hollis, Henry; Fenik, Polina; Pullum, Keelee; Slinger, Michelle; Zamore, Zachary; Zhu, Yan; Anafi, Ron; Veasey, Sigrid
Abstract: Introduction: Chronic sleep disruption (CSD) in young adult mice leads to phenotypes consistent with early (pre-plaque) Alzheimer's Disease (AD), including increased Aβ and hippocampal neuron loss. Mechanisms underlying this injury are not known. Both acute sleep loss and AD activate cofilin, a regulator of actin dynamics. Activated cofilin (AC) in AD mouse models can impart neural injury, increase Aβ, and cofilin translocation to the mitochondria delays cytosolic Ca2+ clearance. We are critically testing the role of AC in chronic short sleep (CSS) and sleep fragmentation (SF) neural injury. Methods: Synapse loss was studied using STED confocal microscopy and Imaris in CSS (n=9) and rested (n=10) mice. Synapses were identified as overlaps of pre- and postsynaptic densities. Percent area of cofilin was measured with FIJI. To further understand if and how wake-induced cofilin activation induces sleep-loss synapse and neural injury, we implanted AAV9CAMKII-GCaMP6f and then GRIN lenses, and later studied CAMKII calcium transients in CA1 of WT controls (n=4) and SF mice (n=4) by measuring GCaMP6f calcium transients. We developed a Shiny R application to analyze the frequency of Ca2+ spikes, ΔF/F0, and the rising and clearance patterns of spikes. To directly test cofilin's role in delayed calcium clearance, we studied the calcium transients in hAPP mice (n=2) after injection of AAV-CAMKII-CofilinS3A to express AC and GCaMP6f. All data were analyzed with two-way ANOVA or unpaired t-tests. Results: Results reveal significant synapse loss in CA1 of CSS mice (CSS=48.8±10.3; Rested=83.4±8.4), t(16)=2.63, p<0.02, and increased cofilin activation (AC=19.8±3.41; Rested=8.76±1.95), t(16)=8.43, p<0.0001. SF mice reveal an increase in NREM sleep firing rates, F(1, 1)=22.0, p<0.001. In contrast, hAPP-AC mice show significantly increased ΔF/F0, F(1, 1)=356, p<0.0001, prolonged calcium influx, F(1, 1)=18.6, p<0.02, and prolonged calcium clearance duration, F(1, 1)=23.9, p<0.01, but not increased firing frequencies. Conclusion: CSS induces CA1 synapse loss and cofilin activation in WT mice. Increased CAMKII calcium ΔF/F0 occurs through different pathways in SF and AC, suggesting additional factors in CSD neural injury. Support (If Any): NIH AG054104; AG064231